2021
DOI: 10.1111/bjh.17954
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal assessment of adhesion to vascular cell adhesion molecule‐1 at steady state and during vaso‐occlusive crises in sickle cell disease

Abstract: Sickle cell disease (SCD) is characterized by frequent and unpredictable vaso-occlusive crises (VOCs). Sickle erythrocytes (SSRBCs) contribute to VOCs by participating in a series of adhesive events with blood cells and the vascular endothelium. Adhesion assays have been used to evaluate the relationship between SSRBC adhesion and SCD severity. We developed a standardized, clinical flow adhesion assay of whole blood to vascular cell adhesion molecule (FA-WB-VCAM). The objective of this study was to assess the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…No correlation was observed with FA-WB-VCAM measured during VOC. Previous reports suggested that FA-WB-VCAM at clinical baseline as one of the determinants of the overall disease severity [13], with such elevated severity potentially contributing to P-selectin-driven onset of VOC.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…No correlation was observed with FA-WB-VCAM measured during VOC. Previous reports suggested that FA-WB-VCAM at clinical baseline as one of the determinants of the overall disease severity [13], with such elevated severity potentially contributing to P-selectin-driven onset of VOC.…”
Section: Discussionmentioning
confidence: 98%
“…No correlation was observed with FA-WB-VCAM measured during VOC. Previous reports suggested that FA-WB-VCAM at clinical baseline as one of the determinants of the overall disease severity [13], with such elevated severity potentially contributing to P-selectin-driven onset of VOC. Additionally, increased VCAM-1/VLA-4 interactions may lengthen TTR because more adhesive sickle RBCs may become trapped in post capillary venules, further contributing to VOC events.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…15,16 While most of these works have been conducted using blood samples collected at one-time point, some have utilized longitudinal studies to better understand the temporal nature of sickle cell disease on the time scale of weeks and months. 17 Our work is not the rst to use QPI to image sickle cell erythrocytes. Previous studies have used QPI to explore a variety of different research questions.…”
Section: Introductionmentioning
confidence: 97%